Olivia saves the circus - Falconer, Ian, 1959- (New York : Atheneum Books for Young Readers, 2001)
At school, Olivia tells about her summer vacation and how, when she went to the circus and all the performers were out sick, she saved the day, becoming Olivia the Tattooed Lady, Olivia the Lion Tamer, The Amazing Flying Olivia, and more.
"An Anne Schwartz book."
Notable/Best Books (A.L.A.)
School Library Journal starred
Wilson's Children
3.0
K-3.
Keywords: Circus -- Fiction; Pigs -- Fiction; Schools -- Fiction; Circus -- Fiction; Pigs -- Fiction; School stories